Accessing the importance of communication skills in the education service sector with special reference to postgraduate medical students in Malaysia - Naila Aaijaz (2009)
The doctor-patient relationship is central to the delivery of high quality medical care, which to a large extent has been found to depend on high communication skills. We can analyse the importance of communication in various ways, such as how to collect information regarding the patient and how to transmit information to the patient regarding his illness (a crux of medical practice). Based on this information, diagnosis can be made and health care is delivered in an effective manner. This study sought to qualify the current knowledge of postgraduate (PG) medical students in Malaysia about the importance of communication skills in improving their professional skills and handling patients. A cross-sectional study using a self-report questionnaire was conducted among postgraduate medical students. Data analysis was questionnaire based. PG medical students are not tought communications skills as part of the medical syllabus; however, the results suggest that there is a real need to integrate communication skills within the course. This should be linked to the various ethic and religous backgrounds of medical students, into Malaysian medical curriculum. Some recommendation will be based on the study carried out. Some limitations of the study will also be discussed.Nai